2014
DOI: 10.1074/jbc.m114.556266
|View full text |Cite
|
Sign up to set email alerts
|

A Cryptic Polyreactive Antibody Recognizes Distinct Clades of HIV-1 Glycoprotein 120 by an Identical Binding Mechanism

Abstract: Background: Polyreactive antibodies can efficiently neutralize HIV. Results: Heme induces polyreactivity of a human antibody, which recognizes distinct gp120 clades by an identical binding mechanism. Conclusion: Antigen-binding promiscuity of a polyreactive antibody allows recognition of antigen with high molecular heterogeneity. Significance: Characterization of the interaction of polyreactive antibodies with envelope proteins of HIV reveals novel strategies for control of the virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 73 publications
1
51
0
Order By: Relevance
“…Conversely, a broadly neutralizing Ab isolated from an HIV-1-infected patient displayed more discriminative interactions and was not able to recognize all the variants of gp120 included in the study. The results obtained in the latter study also suggest that cofactor-bound Abs use the unique chemistry of the heme molecule to recognize gp120, wherein IgG-bound heme serves as an interfacial bridge to connect Ab and gp120 (31). Importantly, heme and its analogues have been demonstrated to bind to gp120 in the V3 region (46 -49).…”
Section: Heme-induced Reactivitymentioning
confidence: 63%
See 4 more Smart Citations
“…Conversely, a broadly neutralizing Ab isolated from an HIV-1-infected patient displayed more discriminative interactions and was not able to recognize all the variants of gp120 included in the study. The results obtained in the latter study also suggest that cofactor-bound Abs use the unique chemistry of the heme molecule to recognize gp120, wherein IgG-bound heme serves as an interfacial bridge to connect Ab and gp120 (31). Importantly, heme and its analogues have been demonstrated to bind to gp120 in the V3 region (46 -49).…”
Section: Heme-induced Reactivitymentioning
confidence: 63%
“…Previous studies have demonstrated that exposure of some monoclonal Abs to the redox cofactor heme results in acquisition of reactivity to different structurally unrelated antigens (20,31). Spectroscopic analyses revealed that this phenomenon is mediated by binding of the macrocyclic cofactor molecule to the variable region of immunoglobulins (7,31).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations